Saint Louis in 1896. - Fred Graf Engraving Co.; Graf, Fred. (1896)
Bird's-eye-view.; Available also through the Library of Congress Web site as a raster image.; AACR2: 651/1; Perspective map not drawn to scale.; LC Panoramic maps (2nd ed.), 444; Includes illus.